Tingkat Kesesuaian Lahan Bagi Tanaman Padi Berdasarkan Faktor Iklim Dan Topografi Di Kabupaten Merauke - Ruth C Mahubessy (Faculty of Agriculture, Pattimura University, 2014)
Agricultural activity is largely determined by the local climate. Climate plays a vital role in planning agricultural production systems because all of climate elements has a major influence on various physiological processes, the growth and productivity of plants. In determining the suitability of land for food crops, especially rice plant, level slope data and average values of several weather elements such as rainfall, humidity, temperature and dry months that occurred within a year were requires. Having earned an average values of some elements of the weather,the land suitability analysis can be determined by some criteria. Based on the result of land suitability analysis, there is no area with high land suitability (S1), but more than 50% of the area qualifies as a moderate land suitability (S2). This area lies in the western and southern Merauke